2021
DOI: 10.1136/jech-2021-216689
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in population-based hospitalisation rates for myocardial infarction in England: a national database study of 3.5 million admissions, 1968–2016

Abstract: AimTo analyse the timing and scale of temporal changes in rates of hospitalised myocardial infarction (MI) in England by age and sex from 1968 to 2016.MethodsMI admissions for adults aged 15–84 years were identified from electronic hospital data. We calculated age-standardised and age-specific rates, and examined trends using joinpoint.ResultsFrom 1968 to 2016, there were 3.5 million admissions for MI in England (68% men). Rates increased in the early years of the study in both men and women, peaked in the mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Our findings build upon previous studies, that showed declines in myocardial infarction incidence across various populations and several decades [3,[19][20][21][22][23]38]. These improvements likely pertain to better risk factor control and higher uptake of evidence-based preventive treatment [1,2,39,40].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings build upon previous studies, that showed declines in myocardial infarction incidence across various populations and several decades [3,[19][20][21][22][23]38]. These improvements likely pertain to better risk factor control and higher uptake of evidence-based preventive treatment [1,2,39,40].…”
Section: Discussionsupporting
confidence: 85%
“…However, females and the elderly were underrepresented in cardiovascular prevention research historically [15,16], and have differential risk factors for atherosclerotic cardiovascular disease compared to males and younger individuals [17,18]. The most recent studies of myocardial infarction incidence had follow-up through the mid-2010s [19][20][21][22], or reported age-and sex-standardized incidences, thus not showing the age-and sex-specific developments in the incidence of myocardial infarction [23].…”
Section: Introductionmentioning
confidence: 99%
“…
CardioVascular (CV) Disease (CVD) accounts for 25% of all UK deaths [1][2][3][4]. Before developing and applying new or existing CV risk prediction tools [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] for prediction of incident CVD events, it is important to have a description of the baseline characteristics of the patients who experienced a myocardial Infarction (MI) event.
…”
mentioning
confidence: 99%